Blockage of androgen and administration of estrogen induce transdifferentiation of testis into ovary. Issue 1 (April 2017) - Shi, Hongjuan; Gao, Tian; Liu, Zhilong; Sun, Lina; Jiang, Xiaolong; Chen, Lili; Wang, Deshou
Abstract : Induction of sex reversal of XY fish has been restricted to the sex undifferentiated period. In the present study, differentiated XY tilapia were treated with trilostane (TR), metopirone (MN) and glycyrrhetinic acid (GA) (inhibitor of 3β-HSD, Cyp11b2 and 11β-HSD, respectively) alone or in combination with 17β-estradiol (E2) from 30 to 90 dah (days after hatching). At 180 dah, E2 alone resulted in 8.3%, and TR, MN and GA alone resulted in no secondary sex reversal (SSR), whereas TR + E2, MN + E2 and GA + E2 resulted in 88.3, 60.0 and 46.7% of SSR, respectively. This sex reversal could be rescued by simultaneous administration of 11-ketotestosterone (11-KT). Compared with the control XY fish, decreased serum 11-KT and increased E2 level were detected in SSR fish. Immunohistochemistry analyses revealed that Cyp19a1a, Cyp11b2 and Dmrt1 were expressed in the gonads of GA + E2, MN + E2 and TR + E2 SSR XY fish at 90 dah, but only Cyp19a1a was expressed at 180 dah. When the treatment was applied from 60 to 120 dah, TR + E2 resulted in 3.3% of SSR, MN + E2 and GA + E2 resulted in no SSR. These results demonstrated that once 11-KT was synthesized, it could antagonize E2-induced male-to-female SSR, which could be abolished by simultaneous treatment with the inhibitor of steroidogenic enzymes. The upper the enzyme was located in the steroidogenic pathway, the higher SSR rate was achieved when it was inhibited as some of the precursors, such as androstenedione, testosterone and 5α-dihydrotestosterone, could act as androgens. These results highlight the key role of androgen in male sex maintenance.